2004
DOI: 10.1103/physrevb.69.085308
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of photoluminescence bands inZn1xCdxSet al.

Abstract: We have studied the temperature dependence of the photoluminescence ͑PL͒ spectra of molecular beam epitaxy grown ultrathin Zn 1Ϫx Cd x Se/ZnSe quantum wells with random and inhomogeneous Cd distributions over cation sublattice within the temperature interval 2-300 K. Depending on the Cd concentration, the PL band maximum position E max PL (T) follows either a ''normal'' or an ''anomalous'' ͑known as ''S-shaped''͒ temperature dependence. We have analyzed both dependences in detail for a model of an island ensem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 60 publications
5
33
0
4
Order By: Relevance
“…5 We further conclude from our data that it does not depend significantly on the NC shape. Also ⌰ is close to the value reported for the bulk, 5,18 although the smaller value of ⌰ for NDs, which corresponds to some average phonon energy, might indicate increased coupling of the optical transition to lower energy acoustic phonons and reduced coupling to LO phonons compared to the other shapes. It could also be a consequence of the reduced volume.…”
Section: Temperature Effects On the Spectral Properties Of Colloidal supporting
confidence: 82%
“…5 We further conclude from our data that it does not depend significantly on the NC shape. Also ⌰ is close to the value reported for the bulk, 5,18 although the smaller value of ⌰ for NDs, which corresponds to some average phonon energy, might indicate increased coupling of the optical transition to lower energy acoustic phonons and reduced coupling to LO phonons compared to the other shapes. It could also be a consequence of the reduced volume.…”
Section: Temperature Effects On the Spectral Properties Of Colloidal supporting
confidence: 82%
“…22 To meet technological demands for large scale synthesis, Kim et al reported subkilogram-scale one-pot synthesis of the quantum dots, which involved the use of organic surfactants and solvents. 1 In the current study, the Zn x Cd 1Ϫx Se/C nanocrystals were synthesized in sealed reactors, without the use of solvents and organic chemicals.…”
mentioning
confidence: 99%
“…Область (I) содержит QDs, для основного экситонного уровня, в которых нет соответствующего возбужденного уровня QDs-акцепторов и, следовательно, специфический меха-низм типа FRET 1 с быстрой релаксацией возбуждения на нижний экситонный уровень для них невозможен. Следует отметить, что граница между областью (I) и (II) спектрально приблизительно совпадает с краем подвижности (mobility edge), обсуждаемым ранее в ра-боте [9]. Квантовые точки, размеры которых попадают в область (II), могут участвовать в переносе энергии по механизму FRET 1 на возбужденные уровни (2e−1h) в QDs в области (IV).…”
Section: моделирование и анализ результатовunclassified
“…Рассмотрение таких планар-ных массивов в модели разупорядоченных квантовых ям (QW) проблематично, поскольку при низкой темпера-туре рекомбинирующие носители должны быть хорошо локализованы. Согласование этих противоречивых мо-ментов потребовало в работе [9] включения в состав QW нано-островков различных типов -изолированных, перекрывающихся и метастабильных.…”
Section: Introductionunclassified